USE OF DIGITAL TECHNOLOGIES IN WOMEN'S DRESS DESIGN - PAVLIUK, Anna; KERNESH, Victoria (Herald of Khmelnytskyi National University. Technical sciences, 2022)
In the modern and dynamic life conditions of the metropolis, business is gaining momentum of reformatting, as the military events in Ukraine and the pandemic have brought fashion to a new level of development and functioning to maintain the competitiveness of manufacturers and to satisfy consumers. In order to constantly update the assortment, companies have to quickly respond to market changes, fashion trends and the development of innovations in the field of computer technology and software, because now most areas of human activity have gone digital. Properly organized and planned design and technological preparation of production using automated CAD design is of great importance to increase business efficiency and competitiveness of a specific manufacturer's products. The article researched, analyzed and provided a comparison of the possibilities of using modern software products, namely programs for visualizing products of the fashion industry on a virtual mannequin. Such programs as CLO3D, Browzwear, "Electronic Mannequin", Marvelous Designer, OptiTex 11, Vidya Assyst were considered. The capabilities of the CLO3D program were demonstrated and a comparison of the virtual product and the finished sample was made. It was determined that the programs CLO3D, Browzwear, "Electronic mannequin" are intended for visualization of products and organization of work at enterprises, because the possibility of printing patterns gives a great advantage in the automation of production, they have a wide selection of materials and a range of functions to optimize work in production. Programs like Marvelous Designer, Vidya Assyst are for marketing purposes, animation creation and product presentation. We came to the conclusion that the OptiTex 11 program has insufficient realism in the execution of 3D products due to the lack of variety of materials and has an outdated interface. The expediency of this development has been proven in a theoretical and practical way.
Keywords: virtual mannequin; product visualization; 3D technologies; 3D modeling; CLO3D; Browzwear; "Electronic mannequin"; Marvelous Designer; OptiTex 11; Vidya Assyst